2008
DOI: 10.1002/dvdy.21746
|View full text |Cite
|
Sign up to set email alerts
|

Definitive erythropoiesis in chicken yolk sac

Abstract: The first wave of erythropoiesis in amniotic animals generates all primitive erythrocytes and takes place exclusively in yolk sac mesoderm. It is less clear, however, to what extend and for how long the yolk sac contributes to the second wave of erythropoiesis which gives rise to definitive erythrocytes for later embryonic and adult use. Here, we examine the initiation, duration, and site of definitive erythrocyte formation in chicken yolk sac. We show that the earliest definitive erythrocytes are generated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 51 publications
2
21
0
Order By: Relevance
“…Chick/quail and chick/chick chimera studies (Beaupain et al, 1979;Dieterlen-Lievre, 1975;Dieterlen-Lievre et al, 1976;Lassila et al, 1978;Lassila et al, 1982;Martin et al, 1978) and chick/chick parabiotic studies (Metcalf and Moore, 1971;Moore and Owen, 1965; indicated that, at least during the first few days of definitive erythrocyte generation, the source of cells is mainly yolk sac-derived. At about the same time, if not earlier, intraembryonic hematopoietic cells have been observed in association with the dorsal aorta (DieterlenLievre and Martin, 1981;Jaffredo et al, 2003;Jaffredo et al, 2005;Jaffredo et al, 2000;Jaffredo et al, 1998;Jordan, 1916;Nagai and Sheng, 2008;Olah et al, 1988;Pardanaud et al, 1996). A number of questions can be asked, for instance, about whether dorsal aorta-derived hematopoietic cells undergo definitive erythropoiesis either in circulation or in the yolk sac niche; whether yolk sac-derived hematopoietic cells can find their way to the dorsal aorta; and what is the exact type of cells from the yolk sac that contribute to early definitive erythropoiesis.…”
Section: Transition From Primitive To Definitive Wavementioning
confidence: 87%
See 2 more Smart Citations
“…Chick/quail and chick/chick chimera studies (Beaupain et al, 1979;Dieterlen-Lievre, 1975;Dieterlen-Lievre et al, 1976;Lassila et al, 1978;Lassila et al, 1982;Martin et al, 1978) and chick/chick parabiotic studies (Metcalf and Moore, 1971;Moore and Owen, 1965; indicated that, at least during the first few days of definitive erythrocyte generation, the source of cells is mainly yolk sac-derived. At about the same time, if not earlier, intraembryonic hematopoietic cells have been observed in association with the dorsal aorta (DieterlenLievre and Martin, 1981;Jaffredo et al, 2003;Jaffredo et al, 2005;Jaffredo et al, 2000;Jaffredo et al, 1998;Jordan, 1916;Nagai and Sheng, 2008;Olah et al, 1988;Pardanaud et al, 1996). A number of questions can be asked, for instance, about whether dorsal aorta-derived hematopoietic cells undergo definitive erythropoiesis either in circulation or in the yolk sac niche; whether yolk sac-derived hematopoietic cells can find their way to the dorsal aorta; and what is the exact type of cells from the yolk sac that contribute to early definitive erythropoiesis.…”
Section: Transition From Primitive To Definitive Wavementioning
confidence: 87%
“…From E2 to E5, yolk sac vasculature undergoes at least two phases of remodeling. Hemodynamic changes initiated by heart pulsation remodels early vascular plexus into arterial and venous trees between E2 and E3, followed by the remodeling from two-dimensional apposing arterial/venous trees to a three-dimensional paired arterial/venous network between E3 and E5 (Eichmann et al, 2005;Gonzalez-Crussi, 1971;le Noble et al, 2004;Nagai and Sheng, 2008;Van Mierop and Bertuch, 1967) (Fig. 4).…”
Section: Sources Of Early Definitive Erythrocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, our findings must be compared with classical data on avian hematopoietic ontogenesis (28). It remains to be determined whether mammalian and avian de novo hematopoiesis differ significantly or whether a closer look at the presumed sites of blood-cell generation in chicken would reveal a more prominent role for the avian yolk sac (29).…”
Section: Discussionmentioning
confidence: 99%
“…Weber et al, 2000;Storz et al, 2008;Runck et al, 2009), the isoHb differentiation is not associated with any discrete differences in the developmental timing of expression. The two lizard-specific -globin paralogs exhibit subtle changes in expression during the course of prenatal development, but the pattern appears to be qualitatively different from the more discrete gene switching that characterizes the ontogenetic regulation of Hb synthesis in other tetrapod vertebrates (Banville and Williams, 1985a;Banville and Williams, 1985b;Hardison, 2001;Nagel and Steinberg, 2001;Fuchs et al, 2006;Nakazawa et al, 2006;Alev et al, 2008;McIntyre et al, 2008;Nagai and Sheng, 2008;Alev et al, 2009). …”
Section: Expression Of -Chain Isohbsmentioning
confidence: 99%